Comparison of Angiotensin-Converting Enzyme Inhibitor (ACEI) and Angiotensin Receptor Blocker (ARB) for Heart Failure Treatment in Congenital Heart Diseases with Left-to-Right Shunt - Alit Utamayasa; Mahrus Ahmad Rahman; Teddy Ontoseno; Budiono budiono (The Prodia Education and Research Institute (PERI), 2020)
BACKGROUND: The angiotensin-converting enzyme inhibitors (ACEIs) have become the forefront of heart failure treatment for more than a decade. Currently, angiotensin receptor blockers (ARBs) are thought to have similar effectiveness. This study aimed to compare the impact of captopril, one of ACEI, and valsartan, one of ARB, on clinical presentation and echocardiographic, electrocardiographic, and chest x-ray improvement in patients with left-to-right shunt congenitalheart diseases.METHODS: This study used a double-blind randomized controlled trial of captopril and valsatran to children with left-to-right shunt congenital heart diseases who suffer from heart failure in the Dr. Soetomo General Hospital, Surabaya, Indonesia. Pediatric heart failure scores, echocardiography, electrocardiography (ECG), and chest photographs were examined at the beginning of the study and after 30 days of treatment.RESULTS: A decrease in pediatric heart failure scores were showed after the administration of ACEI (7.06±2.04 vs. 4.75±2.43; p<0.0001; 95% CI: −2.98 - 1.65); ARB (6.81±2.25 vs. 3.94±1.98; p<0.0001; 95% CI: −3.76 to 1.98). The echocardiography examination, an increase in left ventricular end-diastolic volume (LVEDV), left ventricular ejection fraction (LVEF), % fractional shortening (FS), and left ventricular (LV) dimension occurred after the administration of ACEI and ARB. The values also didn’t significantly differrent between the two groups. The ECG evaluation showed a decrease in heart rate frequency after the administration of ACEI (117.75±14.67 vs. 109.63±17.59; p=0.039; 95% CI: −15.78 to −0.46) and ARB (117.10±21.86 vs.108.6±20.66; p=0.006; 95% CI: −14.17 to −2.83).CONCLUSION: ARB showed better outcome in clinical condition, echocardiography, ECG, and chest radiographs.KEYWORDS: captopril, valsartan, heart failure, congenital heart disease, left to right shunt